2017
DOI: 10.1186/s13006-017-0141-x
|View full text |Cite
|
Sign up to set email alerts
|

Rural-urban differences on the rates and factors associated with early initiation of breastfeeding in Nigeria: further analysis of the Nigeria demographic and health survey, 2013

Abstract: BackgroundThis study investigates and compares the rates and factors associated with early initiation of breastfeeding (EIBF) within one hour of birth in rural and urban Nigeria.MethodsData from the 2013 Nigeria Demographic and Health Survey (NDHS) were analyzed. The rates of EIBF were reported using frequency tabulation. Associated factors were examined using Chi-Square test and further assessed on multivariable logistic regression analysis.ResultsThe rates of EIBF were 30.8% (95% confidence interval [CI] 29.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
39
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(54 citation statements)
references
References 30 publications
13
39
1
1
Order By: Relevance
“…The finding on the timely initiation of breastfeeding in this study is comparable with that of other studies [9,16]. However, the prevalence of timely initiation of breastfeeding in this study is lower than that of similar studies [14,15], and higher than findings in other studies [16][17][18][19]. Also, the prevalence of timely initiation of breastfeeding reported in this study generally is well above the 50% target of timely initiation of breastfeeding recommended by WHO to be achieved by all countries by 2025 [20].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The finding on the timely initiation of breastfeeding in this study is comparable with that of other studies [9,16]. However, the prevalence of timely initiation of breastfeeding in this study is lower than that of similar studies [14,15], and higher than findings in other studies [16][17][18][19]. Also, the prevalence of timely initiation of breastfeeding reported in this study generally is well above the 50% target of timely initiation of breastfeeding recommended by WHO to be achieved by all countries by 2025 [20].…”
Section: Discussionsupporting
confidence: 86%
“…Nonetheless, since the survey was selfreported, there is the possibility of recall bias. Also, given the secondary nature of the data we used, we had no control over the measurement and selection of variables which led to the omission of variables such as marital status of mother, mode of delivery, place of delivery, mother's use of ANC services, ethnicity, mother's ownership of a house and mother's occupation which have been shown to influence the practice of timely initiation of breastfeeding elsewhere [9,17,18,22,23].…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…The following independent variables were included in the analysis: age of the woman in years (15-24, 25-34, or 35-49), marital status (never married, separated/divorced/widowed, or married/ cohabiting), level of education (no formal school/primary, secondary, or higher), wealth index quintiles (poorest, poorer, middle, richer, or richest), region of residence (Peru is divided into 3 regions: the coastal region, near the Pacific coastal line [including Lima, the country's capital city]; the highlands region of the Andes; and the jungle, where the Amazon rainforest is located), place of residence (urban or rural), cesarean section (yes or no), place of delivery (private health facility, public health facility, or other), birth order (first, second or third, or fourth or higher), size of the child at birth (small, medium, or large), sex of the newborn (female or male), type of pregnancy (multiple or single), number of prenatal visits (0-3, 4-7, or 8 or more), utilization of breastfeeding training (yes or no), ethnic self-identification (White/mixed-race/ other, Native, or Black/Brown/Zambo), and head of the household (yes or no). The selection and inclusion of these variables was based on an epidemiological criterion and on variables reported in previous ENDES-based studies [19][20][21][22][23].…”
Section: Variables and Measurementsmentioning
confidence: 99%
“…Bivariate analysis in the present study shows that there is a significant relationship between place of residence and non-EBF (43.0% of the non-EBF women lived in urban areas, versus 33.9% in rural areas [P = 0.033]), while there isn't a significant relationship between place of residence and non-EIBF ( Table 2). Adewuyi et al (19) and Pandey et al (26) reported that the non-EIBF rate is lower in women from rural residences, based on DHSs. The significance of the relationship between place of residence and non-EBF in the present study disappeared in multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Mode of delivery is among the factors that play an important role in breastfeeding practices. C/S can negatively affect the physiology of lactation and can cause adverse events that hinder maternal contact with the neonate, resulting in intolerable post-surgical maternal pain and an increase in the level of need for intensive care required by neonates, both of which can negatively affect breastfeeding (10,14,(18)(19)(20). The present study's multivariate analysis indicates that maternal level of education, residential region and mode of delivery are significantly related to non-EIBF and that mode of delivery has a significant relationship with non-EBF.…”
Section: Discussionmentioning
confidence: 99%